Eksplorasi Fundamental Cryptocurrency dalam Volatilitas Harga - Chrisna Satya Wardhana (Jurnal Syntax Admiration, 2024)
This research aims to comprehensively explore the fundamental factors that influence cryptocurrency price volatility, and apply them to adoption, regulation and investment strategies. The fundamental factors explained include supply, demand, mining activity, transaction fees, block size, blockchain technology, and context mechanisms. This research uses a qualitative and quantitative approach with literature study and secondary data analysis. The research results show that cryptocurrency price volatility is significantly influenced by the interaction of supply and demand, mining activity as reflected in the hash rate, as well as transaction costs and block size in the blockchain network. Additionally, blockchain technology and the context mechanisms used also contribute to price volatility. High price volatility hinders the use of cryptocurrencies as a stable medium of exchange and investment instrument.